ESTIMASI NILAI HERITABILITAS DAN NILAI PEMULIAAN BOBOT SAPIH KAMBING SAPERA DI CV. BHUMI NARARYA FARM, KECAMATAN TURI KABUPATEN SLEMAN YOGYAKARTA - Astuti, Mita Putri Astuti; Rahmawati, Resti Yuliana; Winurdana, Alfan Setya (AVES: Jurnal Ilmu Peternakan, 2023)
The purpose of this research was to determine heritability and breeding values of the weaning weight of sapera goats at CV. Bhumi Nararya Farm, Turi District, Sleman Regency, Yogyakarta. The samples used were data from 5 males, 70 females, and 32 young sapera goats. The method used in this study is a survey. The data taken are primary and secondary data. The results of the study for the estimation of the heritability value of the weaning weight of sapera goats were 0.24 ± 0.25, and the highest breeding value was 15,253. The conclusion from the research that has been done at CV. Bhumi Nararya Farm on sapera goats is that the heritability value of weaning weight belonging to the medium category, with a value of 0.24 ± 0.25, can be used as a selection tool, provided the selection program is carried out strictly and continuously, to improve the genetic quality of livestock in an effort to increase goat productivity. The highest breeding value from the estimated heritability value of the weaning weight of Sapera goats in CV. Bhumi Nararya Farm is 15.253.